An apple a day keeps the doctor away? - a review of health benefits of apples - Piotr Bator; Michał Razik; Patrycja Rozwadowska; Jan Ramian; Jakub Rybak; Barbara Magiera; Karol Magiera; Martyna Grabowska-Szczurek; Alicja Grabarczyk; Wiktor Razik (Kazimierz Wielki University, 2024)
Introduction and purpose: Apples are a widely consumed fruit globally and are known to be a great source of nutrition. Studies have shown that apples contain high levels of antioxidants, dietary fiber, and vitamins that contribute to numerous health benefits. This paper aims to provide a comprehensive review of the impact of apples on human health. State of knowledge: The paper reviews the current literature on the health benefits of apples, focusing on their impact on various health conditions such as cancer, cardiovascular diseases, diabetes, and obesity. Additionally, it examines the role of apples in improving intestinal, immune, and cognitive function. The paper also discusses the potential mechanisms by which apples exert their health benefits, such as high levels of flavonoids, polyphenols, and dietary fiber. Summary: In conclusion, the vast body of evidence reviewed in this paper supports the notion that consuming apples regularly can contribute to better health outcomes. They may help reduce the risk of chronic diseases, such as cancer, cardiovascular diseases, and diabetes, as well as promote healthy gut microbiota and immune function. Despite the controversy surrounding the use of pesticides in apple cultivation, the benefits of consuming apples outweigh the risks. Therefore, it is highly recommended to include apples as part of a balanced and nutritious diet to promote optimal health and wellbeing. As the saying goes, "An apple a day keeps the doctor away".